Parental separation and children’s education – changes over time? - Kailaheimo-Lönnqvist, Sanna; Jalovaara, Marika; Myrskylä, Mikko (Germany, 2026)
Objective and background
The association between parental separation and children’s education has been widely studied,
but mostly at a single time point, for one educational outcome at a time and for marital
dissolution only. We examine whether the (generally negative) association has changed across
cohorts for several educational outcomes and whether the association differs by parental union
type (marriage, cohabitation) and family background (parental education). Due to high rates of
separation, the association with children’s education could have weakened over time.
Methods
We use Finnish total population register data. We focus on child cohorts born between 1987
and 2003 (N=1,004,823) and analyse grade point averages, secondary education and tertiary
education using linear probability models with standard errors clustered within families.
Results and conclusion
The association between parental separation and educational achievement is negative and has
remained similar across the birth cohorts. Differences according to parental union type and
socioeconomic family background are small and do not exhibit changes over time. The stability
of the association over time suggests that the consequences of parental separation on children’s
education have not changed, even though attitudes towards separation may have changed.